دور عوامل البيئة الداخلية في تحسين أداء العاملين دراسة تحليلية آلراء المديرين في منظمة إعادة التأهيل, والتعليم و صحة المجتمع) (REACH(فرع أربيل - Aso Kurdo Ahmed; Mozkan Ibrahim Hasan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
The re implementation of internal factors is significant to improve the performance of employees in organizations that play a central role in improving the performance of employees. To achieve that, I have designated the research in Rehabilitation, Education and Community Health in Erbil. The research adopted the questionnaire as the main tool for collecting data and information in the field. A questionnaire was distributed to (35) managers. All questionnaires were retrieved and all were valid for analysis. The research sought to describe the research variables and diagnose them to test the hypotheses related to the relationships and influence between the factors of the internal environment as an independent variable in terms of dimensions (organizational structure, organizational culture, organizational resources and leadership) and the performance of workers as a deliberate variable and dimensions (training Confidence and Response). In order to test the research plan and its hypotheses, several statistical methods were used (frequency distribution, percentages, mean values, standard deviation, Spearman correlation, agreement ratio, and stepwise regression) using SPSS-V.25. According to this premise, some excitations are necessary to limit the problem of research. To what extent can internal environmental factors contribute to improving the performance of the staff of the researched organization? What is the role of the organizational structure in achieving the performance of employees? The results proved that all hypotheses are achieved to varying degrees, and the research reached a set of conclusions, including the existence of a statistically significant relationship and influence between the factors of the internal environment and the role of the performance of the employees. Factors the performance of the staff of the researched organization increased. The research has come up with a number of proposals, which is necessary for the researched organization; the most important is to pay attention to the internal environment factors in order to improve the performance of the employees of the researched organization. In addition, the researched organization to increase the level of organizational trust by increasing cooperation and based on social relations between managers and workers.